Characterization and Corrosion Resistence of Galvanized Steel//Passivation Compositive/Polyuethane Paint Systems - Di Sarli, Alejandro Ramón (2014)
The corrosion performance of electrogalvanised steel sheets pre-treated with a Cr3+ or Cr+6-based conversion layer and then covered with polyurethane-waterborne topcoat paint has been studied. The pre-treated metallic panels were coated with one of the three tested polyurethane (PU) topcoat paints, in which the dispersion type was the formulation variable. The pigment was TiO2 (rutile) with a PVC value of 10. Before and after the immersion in 0.05 M NaCl (pH 5.70) or 0.1 M Na2SO4 (pH 6.36) solutions, replicates of the different samples were subjected to standardized tests (porosity, gloss and color, hardness, flexibility). During the immersion, blistering and rusting degrees were evaluated through periodical visual inspections, while the coated steel performance was monitored by Electrochemical Impedance Spectroscopy (EIS) measurements. Initial (dry) and final (wet) paint adhesion was also determined. EIS data were interpreted and discussed in terms of the time dependence of the electrical (paint coating) and electrochemical (steel substrate) parameters associated with interfacial processes describing the metal/paint system deterioration. According to the electrochemical properties, visual inspection a standardized tests results, it was concluded that the studied polyurethane-based polymeric films applied on pretreated electrogalvanised steel provided a very effective protection against corrosion as a result of their excellent barrier properties.